HUBUNGAN BUDAYA ORGANISASI DAN PENGHARGAAN TERHADAP MOTIVASI KARYAWAN : STUDI KAUSAL TERHADAP KARYAWAN UNIVERSITAS MEGOUPAK TULANG BAWANG - Effendi, Rustam (Jurnal Manajemen dan Keuangan, 2012)
The aim of this research is to obtain information related to the effect of the organizational culture, and reward on motivations. Survey was conducted in this research with 63 sample of employees selected randomly. Data have been analyzed by path analysis. The findings of this research show that employeesâ trust is affected directly organizational culture as well as motivations. Motivations is affected directly by organizational culture, and as well as employeeâs rewardt. Based on those findings it can be concluded that any concern toward, organizational culture, and employeesâ reward of university of Megoupak have an effect on motivations. Therefore, organizational cultur, and employeesâ reward should be put into strategic planning of human resources development in increasing the motivations of University Megoupak of Tulang bawang, however other variables are necessary to be taken into account properly.Keywords : Organizational Culture, employeeâs Reward, and Motivations